The position of greater palatine foramen in the adult human skulls of North Indian origin. - Renu, C (Department of Surgery, UKM Medical Centre, 2013)
Dentists and Anaesthetists anaesthetize greater palatine nerve at greater palatine foramen, to perform various surgeries on hard palate. But even standard textbooks of Anatomy mention the position of greater palatine foramen in a very general way. Considering the paucity of literature on exact location of greater palatine foramen in North Indians and its variable description in standard textbooks of anatomy and anaesthesiology, following study was felt necessary to be conducted. Various parameters in relation to greater palatine foramen were noted in one hundred adult human skulls of North Indian origin. The dentition was complete with full eruption of third molar teeth. Greater palatine foramen was medial to third molar in most of the skulls seen (47.5%). Greater palatine canal opened vertically downwards in majority of the skulls examined (93.5%). Generally, the palatal vault was “U” shaped. Posterior margin of the foramen was raised in more than 63% skulls.